Pengaruh Perceived Ease Of Use, Perceived Usefulness, Dan Attitude Toward Using Terhadap Purchase Decision Buku Digital Pada Aplikasi Gramedia Digital: Studi Pada Followers Instagram @Gramedia Digital - Nandini Silla Putri; Rumyeni Rumyeni (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The rapid acceleration of digital-based technology has led to a business transformation, particularly within the book publishing industry. This study aims to analyze the influence of perceived ease of use, perceived usefulness, and attitude toward using on purchase decisions of digital books on the Gramedia Digital application. The evaluative reviews still present on this application serve as the basis for conducting this research. This study employs four research hypotheses tested using a quantitative approach. The research instrument utilized is a questionnaire. The population consists of all Gramedia Digital application users throughout Indonesia, reached through a sampling frame of the official Instagram account followers @gramediadigital. Samples were selected using a non-probability sampling method with a purposive sampling technique, resulting in 96 respondents. The criteria for respondents were individuals who had previously made a purchase or subscribed to the Gramedia Digital application. Statistical testing was performed using IBM Statistical Software for the Social Sciences (SPSS) version 27. The results of this study indicate that, partially, the three variables, Perceived Ease of Use, Perceived Usefulness, and Attitude Toward Using have a positive and significant influence on Purchase Decisions. Simultaneously, these three independent variables also significantly affect Purchase Decisions, with an Fcount of 57.871 > Ftable 2.704. Based on the coefficient of determination test, the independent variables contribute 65.4% to the dependent variable, while the remaining 34.6% is influenced by other variables not examined in this study